2021
DOI: 10.32737/0005-2531-2021-4-43-48
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Organosilicon Episulfides

Abstract: A study was made of the interaction of thiourea with saturated and unsaturated organosilicon oxiranes in absolute methyl alcohol in a medium of potassium hydroxide, and methods were developed for the synthesis of unsaturated and unsaturated organosilicon silicides with a yield of 65–75%.The studies carried out revealed that the synthesized organosilicon episulfides are very reactive compounds and can react with nucleophilic and electrophilic reagents, while forming the corresponding silicon derivatives. The IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The spin-spin interaction J (H A , H B ) value is 13.5-14.5 Hz which indicates a trans-structure, and the triorganosilyl group is fixed at the peripheral carbon atom of C≡C bond. The investigations revealed that the oxirane groups in the synthesized oxiranosilanes had a high reactivity and easily underwent the interaction with electrophilic and nucleophilic reagents, forming the corresponding silicon derivatives [8][9][10]. In particular, it found that in the course of interaction of compound (III) with diethylamine, the oxirane cycle opening with the formation of the corresponding aminoalcohols with vibration of 2875 cm -1 occured; the interaction of compound (IV) with methanol led to the disappearance of the absorption band at 3060 cm -1 and the appearance of wide band with center 3450 cm -1 belonging to CH-group, associated with intermolecular hydrogen bond in the spectrum of ether alcohol (X), and the interaction of compound (V) with thiourea proceeds by substitution of the oxirane oxygen for sulfur with the formation of thiiranes (XI).…”
Section: Fig1 Ir Spectrum Of 1-methyl-1-phenyl-1-glycidyloxy-3-methyl...mentioning
confidence: 99%
“…The spin-spin interaction J (H A , H B ) value is 13.5-14.5 Hz which indicates a trans-structure, and the triorganosilyl group is fixed at the peripheral carbon atom of C≡C bond. The investigations revealed that the oxirane groups in the synthesized oxiranosilanes had a high reactivity and easily underwent the interaction with electrophilic and nucleophilic reagents, forming the corresponding silicon derivatives [8][9][10]. In particular, it found that in the course of interaction of compound (III) with diethylamine, the oxirane cycle opening with the formation of the corresponding aminoalcohols with vibration of 2875 cm -1 occured; the interaction of compound (IV) with methanol led to the disappearance of the absorption band at 3060 cm -1 and the appearance of wide band with center 3450 cm -1 belonging to CH-group, associated with intermolecular hydrogen bond in the spectrum of ether alcohol (X), and the interaction of compound (V) with thiourea proceeds by substitution of the oxirane oxygen for sulfur with the formation of thiiranes (XI).…”
Section: Fig1 Ir Spectrum Of 1-methyl-1-phenyl-1-glycidyloxy-3-methyl...mentioning
confidence: 99%